The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1620/tjem.241.131
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Game Playing Is Associated with Poor Toothbrushing Behavior among Athletic Children: A Cross-Sectional Study in Miyagi, Japan

Abstract: Dental problems among athletes have been cautioned due to negative impacts not only on their oral health but also on athletic performance. Acquirement of appropriate oral health behavior mainly composed of toothbrushing in childhood can be one of the most important strategies for advancing children's athletic possibilities. Although habits of screen viewing, including game playing, and TV viewing have direct impacts on children's health and behavioral development, little is known about the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…16,17 Another study showed that excessive game playing is associated with poor tooth brushing behavior. 18 However, the results of this study showed that caries in children was related to the media-use time, even if the snacks were adjusted for. Hence, the associations of snacking with caries may only in part be explained by the association between long media use and frequent snacking in children.…”
Section: Association Between Long Hours Of Media Use and Caries In Chcontrasting
confidence: 54%
See 3 more Smart Citations
“…16,17 Another study showed that excessive game playing is associated with poor tooth brushing behavior. 18 However, the results of this study showed that caries in children was related to the media-use time, even if the snacks were adjusted for. Hence, the associations of snacking with caries may only in part be explained by the association between long media use and frequent snacking in children.…”
Section: Association Between Long Hours Of Media Use and Caries In Chcontrasting
confidence: 54%
“…It is thought that a vicious cycle arises in which snacks are eaten while watching television and children want to eat foods with higher risk for caries . Another study showed that excessive game playing is associated with poor tooth brushing behavior . However, the results of this study showed that caries in children was related to the media‐use time, even if the snacks were adjusted for.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In this context, a study in Japanese athletic children showed that excessive game-playing behavior, not TV-viewing behavior, was significantly associated with a lower daily frequency of tooth brushing (less than twice per day. 42 However, the possible relationship between caries and physical activity has so far been neglected. 43 Although the cross-sectional study design is not indicated for the establishment of causal relationships, this type of study is of outmost value to estimate prevalence of the outcomes in a representative sample of the population and it provides useful data for further longitudinal investigations or to monitor oral health conditions of Pelotas' children over time.…”
Section: Discussionmentioning
confidence: 99%